EFEKTIFITAS PEMBERIAN POC LIMBAH BUAH BELIMBING TERHADAP PERTUMBUHAN DAN PRODUKSI CAISIM (BRASSICA JUNCEA L.) - Sianturi, Calvin Yehezkiel; Sumiasih, Inanpi Hidayati; Puspitawati, Mutiara Dewi (Universitas Trilogi, 2022)
Attaqie Farm is a business that combines tourist attractions by giving visitors knowledge of agriculture, otherwise known as agroeducation. The problem with Attaqie Farm Tuban agroeducation is the amount of waste produced from nesting, ripe fruit, and decaying fruit from a pest attack so that it can reduce the a inclination of agro-tourism if it is allowed to under the tree. The aim of the study is (1) to know the content of the star fruit waste (2) to know the effectiveness of the application of liquid organic fertilizer on the Caisim plant, (3) to knowing the best dose of star fruit waste POC on Caisim plants. The research was conducted from August 2021 to November 2021 at Attaqie Farm, Panyuran Village, Palang District, Tuban Regency, East Java. The method used the RAK method (group random design) has a factor of 1 that is, a concentrated liquid organic fertilizer (POC) of 4 levels of p0 = ml/ l, p1 = 25 ml/ l, p2 = 35 ml/ l, p3 = 45 ml/ l. Each experiment was repeated three times with the number of samples consisting of 5 Caisim and was made up of 60 units. Research shows that the POC of the star fruit waste has a c-organic content (3.96 %), nitrogen (0.03 %), c2o (0.03 %), c2o (0.08), s (0.08), and ph (3.8). Giving POC star fruit waste significantly affect the wet weight of caisim. The 25 ml treatment was the best treatment among all treatments in increasing the growth of caisim.